Towards Equity Projecting and Converging the Human Development Index in Indonesia - Wicesa, Nayaka Artha; Setyanti, Axellina Muara; Prestianawati, Silvi Asna (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 1 (2024): Vol. 17, No. 1, Februari 2024 (pp.1-154)DO - 10.24843/JEKT.2024.v17.i01.p07, 2024)
Human development has become an imperative for Indonesia amid the ongoing demographic bonus. However, various challenges persist in the realm of human development in the country, as evidenced by disparitie?s in Human Development Index (HDI) achievements. This research aims to project Indonesia's HDI for the years 2023, 2024, 2035, and the "Golden Indonesia" period in 2045 to discern the developmental trajectory of HDI and its disparities. Additionally, it seeks to measure the convergence of Indonesia's HDI to attain equitable development. The results of the trend projection estimations indicate that Indonesia's HDI is projected to be 73.74 in 2023 and 74.28 in 2024, which is anticipated to fall below the target set by the government, aiming for an HDI of 75.54 in 2024. Indonesia's HDI is projected to reach 80.22 in 2035 and 85.62 in 2045, categorizing it as 'Very High,' aligning with the vision for the Golden Indonesia in 2045. Furthermore, conditional convergence analysis results indicate that it would take 75 years for provinces with lower HDI to catch up with those with higher HDI, achieving zero inequality. Based on the estimation results, it is found that Per Capita Spending on Educational Functions is a significant variable influencing HDI convergence.   Keywords : Human Development Index, Disparity, Convergence, Projection JEL Classification: C01, O11, O15